POLA KOMUNIKASI ORANG TUA PADA PERILAKU ANAK (STUDI DI WILAYAH RT 07/RW01 DESA KUBANG JAYA KECAMATAN SIAK HULU KAB. KAMPAR) - Rosmala Rosmala (Ensiklopedia of Journal, 2020)
The poor quality of communication in the family will have a bad impact on the integrity and harmony in the family itself. For example, the factors that cause deviation in children's behavior are the result of poor interpersonal communication in the family, even the communication patterns of parents to children are wrong so that the child has the wrong association and has bad behavior. This study aims to answer the formulation of the problem with a research focus on how parental communication patterns on children's behavior and inhibiting and supporting factors of parents in fostering children's behavior. This research methodology uses qualitative analysis. The data collection technique was obtained based on observation, interviews, documentation of the literature study of research informants totaling 3 people. The data were analyzed by means of data collection, data reduction, data presentation, and drawing conclusions and verification. From the results of research and discussion, it is concluded that in the communication patterns of parents to children: Communication patterns are permissive; Authoritarian communication patterns; The third communication pattern is a democratic communication pattern. In relation to the third communication pattern, the cause of violence in children is an authoritarian communication pattern. So that interpersonal communication is needed for parents in developing personality and changing children's behavior with a sense of openness (openess); Empathy (Empathy); Support (Supportiveness); Positive taste (positiveness); Equality (Equality). Communication between parents and children is part of social interaction that can be obtained from the family, environment and even formal education. Parents must be wise and precise in providing communication patterns to children so that interpersoanal communication between parents and children gets effective communication in developing children's personalities.